The coupling coordination between health service supply and regional economy in China: spatio-temporal evolution and convergence - Deng, Jing; Song, Qianwen; Liu, Huan; Jiang, Zicheng; Ge, Chengzhi; Li, Dexun (Frontiers in Public Health, 2024)
Background The coordination of health service supply and regional economy is an integral path to promote China’s prosperity. Methods Based on the coupling mechanism of health service supply and regional economy, we sampled the data from 30 provinces in China from 2009 to 2021 in this study and constructed the evaluation index system. Additionally, we calculated the coupling coordination degree (HED) of the two through the coupling coordination degree model. We further used the kernel density estimation, Moran’s I index, and spatial β convergence model to assess the dynamic evolution trends, spatial aggregation effect, and spatial convergence characteristics of coupling coordination. Conclusion (1) HED in China showed a rising trend during the study period but with large regional differences, forming a gradient distribution pattern of “high in the east and low in the west.” (2) The results of Kernel density estimation show that HED has formed a gradient differentiation phenomenon within each region in China. (3) HED has modeled spatial clustering characteristics during the study period, with high-value clusters mainly appearing in the eastern region and low-value clusters appearing in the northwestern region. (4) There are absolute β-convergence and conditional β-convergence trends in HED in China and the three major regions during the study period, but there is an obvious regional heterogeneity in the control factors. The research provides a reference for accurately implementing policies according to different levels of health service supply and economic development, in addition to narrowing the regional differences of the coupling coordination between the regional economy and health service supply.